Wet chemistry route for the decoration of carbon nanotubes with iron oxide nanoparticles for gas sensing - Elnabawy, Hussam M.; Casanova-Chafer, Juan; Anis, Badawi; Fedawy, Mostafa; Scardamaglia, Mattia; Bittencourt, Carla; Khalil, Ahmed S. G.; Llobet, Eduard; Vilanova, Xavier (Beilstein Journal of Nanotechnology, 2019)
In this work, we investigated the parameters for decorating multiwalled carbon nanotubes with iron oxide nanoparticles using a new, inexpensive approach based on wet chemistry. The effect of process parameters such as the solvent used, the amount of iron salt or the calcination time on the morphology, decoration density and nanocluster size were studied. With the proposed approach, the decoration density can be adjusted by selecting the appropriate ratio of carbon nanotubes/iron salt, while nanoparticle size can be modulated by controlling the calcination period. Pristine and iron-decorated carbon nanotubes were deposited on silicon substrates to investigate their gas sensing properties. It was found that loading with iron oxide nanoparticles substantially ameliorated the response towards nitrogen dioxide.
Keywords: benzene detection; doping; gas sensor; metal nanoparticle decoration; multiwalled carbon nanotubes; NO2 detection; room temperature gas sensing; surface modification

(untitled) - Iijima, S. (Phys. B (Amsterdam, Neth.), 2002)

(untitled) - Schönenberger, C.; Forró, L. (Phys. World, 2000)

(untitled) - Kong, J.; Franklin, N. R.; Zhou, C.; Chapline, M. G.; Peng, S.; Cho, K.; Dai, H. (Science, 2000)

(untitled) - Wang, Y.; Yeow, J. T. W. (J. Sens., 2009)

(untitled) - Zaporotskova, I. V.; Boroznina, N. P.; Parkhomenko, Y. N.; Kozhitov, L. V. (Mod. Electron. Mater., 2016)

(untitled) - Abdelhalim, A.; Abdellah, A.; Scarpa, G.; Lugli, P. (Nanotechnology, 2014)

(untitled) - Mudimela, P. R.; Scardamaglia, M.; González-León, O.; Reckinger, N.; Snyders, R.; Llobet, E.; Bittencourt, C.; Colomer, J.-F. (Beilstein J. Nanotechnol., 2014)

(untitled) - Baccar, H.; Thamri, A.; Clément, P.; Llobet, E.; Abdelghani, A. (Beilstein J. Nanotechnol., 2015)

(untitled) - Dilonardo, E.; Penza, M.; Alvisi, M.; Rossi, R.; Cassano, G.; Di Franco, C.; Palmisano, F.; Torsi, L.; Cioffi, N. (Beilstein J. Nanotechnol., 2017)

(untitled) - Zanolli, Z.; Leghrib, R.; Felten, A.; Pireaux, J.-J.; Llobet, E.; Charlier, J.-C. (ACS Nano, 2011)

(untitled) - Peng, S.; Cho, K. (Nano Lett., 2003)

(untitled) - Liu, L.; Zhang, T.; Li, S. C.; Wang, L. Y.; Tian, Y. X. (Chin. Sci. Bull., 2009)

(untitled) - Lao, C. S.; Liu, J.; Gao, P.; Zhang, L.; Davidovic, D.; Tummala, R.; Wang, Z. L. (Nano Lett., 2006)

(untitled) - Cao, Y.; Luo, H.; Jia, D. (Sens. Actuators, B, 2013)

(untitled) - Sun, P.; Wang, W.; Liu, Y.; Sun, Y.; Ma, J.; Lu, G. (Sens. Actuators, B, 2012)

(untitled) - Mirzaei, A.; Hashemi, B.; Janghorban, K. (J. Mater. Sci.: Mater. Electron., 2016)

(untitled) - Zhang, H.; Yu, L.; Li, Q.; Du, Y.; Ruan, S. (Sens. Actuators, B, 2017)

(untitled) - Sonker, R. K.; Yadav, B. C. (J. Taiwan Inst. Chem. Eng., 2017)

(untitled) - Tan, Q.; Fang, J.; Liu, W.; Xiong, J.; Zhang, W. (Sensors, 2015)

(untitled) - Tit, N.; Ezzi, M. M. A.; Abdullah, H. M.; Yusupov, M.; Kouser, S.; Bahlouli, H.; Yamani, Z. H. (Mater. Chem. Phys., 2017)

(untitled) - Clément, P.; Hafaiedh, I.; Parra, E. J.; Thamri, A.; Guillot, J.; Abdelghani, A.; Llobet, E. (Carbon, 2014)

(untitled) - Pistone, A.; Piperno, A.; Iannazzo, D.; Donato, N.; Latino, M.; Spadaro, D.; Neri, G. (Sens. Actuators, B, 2013)

(untitled) - Hua, C.; Shang, Y.; Wang, Y.; Xu, J.; Zhang, Y.; Li, X.; Cao, A. (Appl. Surf. Sci., 2017)

(untitled) - Nitschke, M. (Int. J. Environ. Health Res., 1999)

(untitled) - Salvi, A.; Patki, G.; Liu, H.; Salim, S. (Sci. Rep., 2017)

(untitled) - Hou, P.-X.; Liu, C.; Cheng, H.-M. (Carbon, 2008)

(untitled) - Tsoufis, T.; Douvalis, A. P.; Lekka, C. E.; Trikalitis, P. N.; Bakas, T.; Gournis, D. (J. Nanopart. Res., 2013)

(untitled) - Aroutiounian, V. M. (Lith. J. Phys., 2015)

(untitled) - Grosvenor, A. P.; Kobe, B. A.; Biesinger, M. C.; McIntyre, N. S. (Surf. Interface Anal., 2004)

(untitled) - Gota, S.; Guiot, E.; Henriot, M.; Gautier-Soyer, M. (Phys. Rev. B, 1999)

(untitled) - Biesinger, M. C.; Payne, B. P.; Grosvenor, A. P.; Lau, L. W. M.; Gerson, A. R.; Smart, R. S. C. (Appl. Surf. Sci., 2011)

(untitled) - Sahu, R. K.; Mukherjee, D.; Tiwari, J. P.; Mishra, T.; Roy, S. K.; Pathak, L. C. (J. Mater. Chem., 2009)

(untitled) - Eltouny, N.; Ariya, P. A. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Struzzi, C.; Scardamaglia, M.; Colomer, J.-F.; Verdini, A.; Floreano, L.; Snyders, R.; Bittencourt, C. (Beilstein J. Nanotechnol., 2017)

(untitled) - Roso, S.; Degler, D.; Llobet, E.; Barsan, N.; Urakawa, A. (ACS Sens., 2017)

(untitled) - Lee, Y.-C.; Chueh, Y.-L.; Hsieh, C.-H.; Chang, M.-T.; Chou, L.-J.; Wang, Z. L.; Lan, Y.-W.; Chen, C.-D.; Kurata, H.; Isoda, S. (Small, 2007)